Does Equity Matter in Natural Resource and Livelihood Benefits? Revenue Sharing Policy Implementation at Bwindi Impenetrable National Park, Uganda - Twinamatsiko, Medard; Kagoro, Grace (International Journal of Research and Scientific Innovation, 2024)
This paper presents and interprets key parameters within Revenue Sharing policy implementation framework and links them to people’s livelihood improvement and conservation. This study creates a linkage between equitable distribution of Revenue Sharing projects, people’s livelihood improvement and conservation support. The paper further presents the distribution of projects across various sections of people boardering with Bwindi. Data was analysed both quantitatively and qualitatively to generate frequencies and percentages in order to illustrate the differences. Not all the variables to explain benefit distribution were significant for both livelihood improvement and conservation support. Significant variables included; resource users, ethnicity, gender, proximity from park boundary and homestead distance to vehicle roads and village centres. Results further indicate that projects are not well targeted and there is no equity during implementation. Those who bear the most conservation costs are not well targeted by resource benefits. The paper recommends a Revenue Sharing Equitable Framework and Community Based Monitoring approach in order to improve the policy implementation practice.
Keywords: Equity; Revenue Sharing Policy; Benefit sharing; Integrated Conservation and Development; Revenue Sharing Equitable Framework; Livelihood Improvement